Social media - opportunities and risks - Mohamed, Shafizan (IntechOpen, 2024)
In this era of technology, we find ourselves deeply intertwined in a vast network of digital connections. It’s incredible how a few clicks can bring us access to a wealth of information while simultaneously exposing our lives to a global audience. At the core of this intercon- nected landscape lies social media, a phenomenon that has completely revolutionized our way of communication, business interactions, and navigation in the digital age. This book, Social Media – Opportunities and Risks, takes you on an exploration of this digital frontier—a guided expedition through the potential advantages and dangers that social media presents for individuals, businesses, and society.